Estado actual del marco legal argentino para la caza, producción y comercialización del Lagarto overo (Tupinambis spp.) - Basso, C.P. (2005)
The legislation which regulates the commercialization and use of tegu lizard is very general in most Argentine provinces. In some of them, the legislation is more specific and establishes the hunting season, minimum size of the prey and requirements to be fulfilled by hunters. At national level, The Natural Resources and Human Environment Secretary is responsible for the general guidelines, adopted by the majority of the provinces and adjusted to the particular conditions of each of them. This organization is also responsible for quantifying the volume of leather units to export, fixing the quota for each province, the regulatory framework and the documentation to be carried out by exporters. Tupinambis Project, from the National Program for the Management and Sustainable Use of Wild Species is a fundamental tool for the rational use of this species. The existence of numerous guidelines and regulations, the overlapping of most of them, together with the overlapping of the authorities in charge of their application, determine the convenience of creating unified global guidelines, more complete, simple and clear which would allow the development of a technologically and economically efficient production, sustainable in the ecological environment. This makes necessary a review and a proposal for the creation of new regulations which would fit current needs.